Evaluating the performance of university course units using data envelopment analysis - Sami El-Mahgary; Petri Rönnholm; Hannu Hyyppä; Henrik Haggeén; Jenni Koponen (Cogent Economics & Finance, 2014)
The technique of data envelopment analysis (DEA) for measuring the relative efficiency has been widely used in the higher education sector. However, measuring the performance of a set of course units or modules that are part of a university curriculum has received little attention. In this article, DEA was used in a visual way to measure the performance of 12 course units that are part of a Photogrammetry curriculum taught at Aalto University. The results pinpointed the weakest performing units, i.e. units where the provided teaching efforts might not be adequately reflected in the students' marks in the unit. Based on the results, a single unit was considered to offer poor performance with respect to its teaching resources and was selected as a candidate for revision of its contents. Financial resources were not used as such; instead, the performance of students in previous pre-requisite units was used as the inputs. For clarity, a single output covering the overall student performance in the examined unit was used. The technique should be widely applicable assuming the grade point averages of the students who took the course unit are available along with the marks obtained in the evaluated units and their pre-requisites.
Keywords: 330; data envelopment analysis; performance; efficiency; course units